1991
DOI: 10.2527/1991.6993780x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trypanosoma vivax infection on body temperature, feed intake, and metabolic rate of West African dwarf goats

Abstract: Thirty-two mature dwarf goats weighing between 16 and 30 kg (22.7 +/- 3.7, SD) were used to study the effect of Trypanosoma vivax infection on rectal temperature (RT), feed intake (DMI), and metabolic rate. Sixteen of the goats were infected intravenously with 14 X 10(6) T. vivax each; the 16 others served as controls. Animals were fed at about 1.1 times maintenance. Heat production was measured from 1 wk preinfection to 6 wk postinfection. From data on successive 9-min periods, heat production was calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…The cost due to fever has been shown to differ for goats that were either standing or lying (Van Dam, 1996). The most crucial finding, however, is that of Zwart et al (1991) who found that an increase in heat production due to fever is different, when measured during either day or night. Van Diemen et al (1995) also found time dependent effects on heat production in pigs challenged by Pasteurella multocida.…”
Section: Requirements For Energy During Pathogen Challengesmentioning
confidence: 83%
See 3 more Smart Citations
“…The cost due to fever has been shown to differ for goats that were either standing or lying (Van Dam, 1996). The most crucial finding, however, is that of Zwart et al (1991) who found that an increase in heat production due to fever is different, when measured during either day or night. Van Diemen et al (1995) also found time dependent effects on heat production in pigs challenged by Pasteurella multocida.…”
Section: Requirements For Energy During Pathogen Challengesmentioning
confidence: 83%
“…It has been observed that during pathogen challenges heat production was increased, while food intake and energy retention were reduced e.g. Verstegen et al (1991) and Zwart et al (1991). This effect, however, appears to be both pathogen and dose specific.…”
Section: Partitioning Of Scarce Protein and Energy Resources During Pmentioning
confidence: 94%
See 2 more Smart Citations
“…Zwart et al (15) found that the reduction in feed intake of West African Dwarf Goats infected with Tvivax was very individual.…”
Section: Introductionmentioning
confidence: 99%